Pengembangan Instrumen Penilaian Autentik Pada Materi Segiempat Kelas VII - Efuansyah - Efuansyah; Reny - Wahyuni (Suska Journal of mathematics Education, 2018)
This research aims to produce authentic assessment instruments in mathematics learning materials plan geometry class VII in terms of aspects of validity and practicality as well as to determine the potential effect. This study uses research development methods (development research) type of formative research involving 32 seventh grade students of SMP Negeri 24 Palembang. In this study a series of instruction developed through several stages of self evaluation, expert reviews and one-to-one, small group, and field tests. This research produces authentic assessment on the material properties of the material, the circumference and area of a rectangle. This study includes a series of learning consists of two activities on properties and circumference & area of a rectangle. The results of the development of authentic assessment instruments shows that with them knowing that they are assessed by three aspects (cognitive, affective, and psychomotor) students are very enthusiastic to learn, able to work on the problems with a good, brave respond and put forward the idea of both written and verbal are associated with a square long.